2019
DOI: 10.1042/bsr20181548
|View full text |Cite
|
Sign up to set email alerts
|

Association between the estrogen receptor α gene polymorphisms rs2234693 and rs9340799 and severe and mild pre-eclampsia: a meta-analysis

Abstract: This meta-analysis was performed in order to determine the associations between the estrogen receptor α (ESR1) gene PvuII site (-397T/C, rs2234693) and XbaI site (-351A/G, rs9340799) polymorphisms with severe and mild pre-eclampsia. Eligible studies were identified by searching PubMed, Medline, Embase, China National Knowledge Infrastructure (CNKI), and WanFang databases until May 2018. The pooled odds ratio (OR) and 95% confidence interval (CI) were used to calculate the associations. Six articles (consisting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 24 publications
0
8
0
2
Order By: Relevance
“…Previously, loci rs2234693 and rs9340799 associated with IUGR were also reported as candidate for preeclampsia [28][29][30], age of menarche [31], precocious puberty [32], height at menarche [33], premature ovarian failure [34], endometriosis [35], breast cancer [36], type II diabetes mellitus [37]. Specifically, Molvarec [28] reported the GG genotype of the rs9340799 was associated with a lower risk of IUGR in patients with severe preeclampsia while the homozygous TA haplotype carriers of ESR1 rs2234693 and rs9340799 polymorphisms showed an increased risk of severe preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, loci rs2234693 and rs9340799 associated with IUGR were also reported as candidate for preeclampsia [28][29][30], age of menarche [31], precocious puberty [32], height at menarche [33], premature ovarian failure [34], endometriosis [35], breast cancer [36], type II diabetes mellitus [37]. Specifically, Molvarec [28] reported the GG genotype of the rs9340799 was associated with a lower risk of IUGR in patients with severe preeclampsia while the homozygous TA haplotype carriers of ESR1 rs2234693 and rs9340799 polymorphisms showed an increased risk of severe preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…Although the etiology of PE is considered to be multifactorial, genetic factors are thought to be strong determinants of this disease [4,6]. Early studies reported that VEGF genes were associated with vascular growth and endothelial dysfunction, which may somewhat interpret the development of PE.…”
Section: Discussionmentioning
confidence: 99%
“…Although its etiology has not been well recognized, PE is now regarded as the result of the combined effect of multiple factors [4,5]. According to the results of the several epidemiological studies, PE has a substantial heritable component, which is estimated to be a major effect [4,6].…”
Section: Introductionmentioning
confidence: 99%
“…This meta-analysis indicated that the PvuII and XbaI polymorphisms were not associated with the risk of endometriosis [23]. Results of meta-analysis which studied the relation between ESR1 gene polymorphism (-351A/G and -397T/C variants) demonstrated the increased risk of severe preeclampsia in the carriers of GG genotype (XbaI -351A/G polymorphism) and no association of the ESR1 gene PvuII -397T/C and XbaI -351A/G polymorphisms with severe and mild preeclampsia [24].…”
Section: Discussionmentioning
confidence: 99%